Contemporary and Historical Muslim Scholars as Portrayed by the Ethiopian Islamic Press in the 1990’s - Gori, Alessandro (Aethiopica, 2005)
The article aims at giving some information about Ethiopian Muslim scholars of the past century, so to enhance our general knowledge of Ethiopian Islam, and, moreover, to contribute to a better prosopographical understanding of the Muslim presence in Ethiopia. In this endeavour, it explores the data scattered in Ethiopian Islamic periodical press, which flourished in that country after the fall of the Derg regime in 1991. In particular, the monthly magazine Bilal, which contains in almost every issue a biographical note devoted to some learned man of the recent past, is used to collect material on the scholars. Biographical articles in Amharic and Arabic which appeared in the magazine are summarized and commented upon.